Geography-Dependent Horizontal Gene Transfer from Vertebrate Predators to Their Prey. (11th April 2022) - Kambayashi, Chiaki; Kakehashi, Ryosuke; Sato, Yusuke; Mizuno, Hideaki; Tanabe, Hideyuki; Rakotoarison, Andolalao; Künzel, Sven; Furuno, Nobuaki; Ohshima, Kazuhiko; Kumazawa, Yoshinori; Nagy, Zoltán T.; Mori, Akira; et al.
Abstract: Horizontal transfer (HT) of genes between multicellular animals, once thought to be extremely rare, is being more commonly detected, but its global geographic trend and transfer mechanism have not been investigated. We discovered a unique HT pattern of Bovine-B (BovB) LINE retrotransposons in vertebrates, with a bizarre transfer direction from predators (snakes) to their prey (frogs). At least 54 instances of BovB HT were detected, which we estimate to have occurred across time between 85 and 1.3 Ma. Using comprehensive transcontinental sampling, our study demonstrates that BovB HT is highly prevalent in one geographical region, Madagascar, suggesting important regional differences in the occurrence of HTs. We discovered parasite vectors that may plausibly transmit BovB and found that the proportion of BovB-positive parasites is also high in Madagascar where BovB thus might be physically transported by parasites to diverse vertebrates, potentially including humans. Remarkably, in two frog lineages, BovB HT occurred after migration from a non-HT area (Africa) to the HT hotspot (Madagascar). These results provide a novel perspective on how the prevalence of parasites influences the occurrence of HT in a region, similar to pathogens and their vectors in some endemic diseases.